2014
DOI: 10.1007/s10482-014-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China

Abstract: An alkalitolerant, thermotolerant and Gram-stain negative bacterium, designated strain YIM 78007(T), was isolated from an alkaline geothermal soil sample from Hehua hot spring, Tengchong, Yunnan province, south-west China. Cells of strain YIM 78007(T) were observed to be aerobic and short rod-shaped. The colonies were observed to be orange-red, convex and circular. 16S rRNA gene sequence-based phylogenetic analysis showed that strain YIM 78007(T) clustered with members of the genus Roseomonas (with similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Rihs et al (1993) reported that the DNA G+C content of the genus Roseomonas ranges from 65 to 71 mol%. However, Kim et al (2013) showed the DNA G+C content of R. aerophila was 73.0 mol%, slightly above values previously reported, and Dong et al (2014) reported a 63.0 mol% DNA G+C content for R. alkaliterrae, a value that was slightly below values for species in the genus Roseomonas. From a literature review, the highest content for a IP: 54.202.233.140…”
mentioning
confidence: 42%
See 4 more Smart Citations
“…Rihs et al (1993) reported that the DNA G+C content of the genus Roseomonas ranges from 65 to 71 mol%. However, Kim et al (2013) showed the DNA G+C content of R. aerophila was 73.0 mol%, slightly above values previously reported, and Dong et al (2014) reported a 63.0 mol% DNA G+C content for R. alkaliterrae, a value that was slightly below values for species in the genus Roseomonas. From a literature review, the highest content for a IP: 54.202.233.140…”
mentioning
confidence: 42%
“…gilardii KACC 11652 T (Dong et al, 2014) and other members of the genus Roseomonas (Gallego et al, 2006). The level of DNA-DNA relatedness between strain PN2 T and the closest related species, R. mucosa ATCC BAA-692 T , was 27 %, which is well below the 70 % cut-off point for recognition of genomic species (Wayne et al, 1987).…”
Section: Roseomonas Soli 5n26 T (Jn575264)mentioning
confidence: 99%
See 3 more Smart Citations